Enhancing Student’s Persuasive Writing Achievement Using Internet Meme Pictures - Jihad, Naufal Ibnu; Rustandi, Andi; Tarwana, Wawan (Universitas Galuh, 2025)
The purpose of this study was to investigate whether or not: (1) there was a significant difference in Persuasive Writing achievement among the eleven grade students of one high school in Calipari Cilacap, Central Java was taught by using internet meme pictures and (2) there was no significant difference in Persuasive Writing achievement between the students who were treated using internet meme pictures and those who were not. There were 40 students of XI MIPA 1 and XI MIPA 2 as the sample of this study. In data collection, each group was treated with a pre-test and post-test of writing. The data were processed using Paired Sample t-test and Independent Sample t-test in SPSS version 35. The results of Paired Sample t-test revealed that there was a significant difference in Persuasive Writing achievement before and after students were taught using the internet Meme Pictures. The result from the dependent Sample t-test of the post-test in both experimental and control groups revealed that there was a significant difference in Persuasive Writing achievement between the students who were treated using Internet Meme Picture and those who were not as the P-value both of Paired Sample t-test and Independent Sample t-test results were lower than 0.05 (0.000 < .05).